2021
DOI: 10.1155/2021/9450843
|View full text |Cite
|
Sign up to set email alerts
|

Silencing IL12p35 Promotes Angiotensin II-Mediated Abdominal Aortic Aneurysm through Activating the STAT4 Pathway

Abstract: Background and Purpose. Abdominal aortic aneurysm (AAA) is a chronic inflammatory disorder and the important causes of death among men over the age of 65 years. Interleukin-12p35 (IL12p35) is an inflammatory cytokine that participates in a variety of inflammatory diseases. However, the role of IL12p35 in the formation and development of AAA is still unknown. Experimental Approach. Male apolipoprotein E-deficient (Apoe-/-) mice were generated and infused with 1.44 mg/kg angiotensin II (Ang II) per day. We found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Wang et al recently reported that IL-12p35 regulates IL-6 through the signal transducer and activator of transcription 4 (STAT4) pathway in the inflammatory process of AAA. They also confirmed that IL-6 plays a role in inflammation in AAA (39). However, another study showed that IL-6 has a limited contribution to inflammation in AAA (37).…”
Section: Discussionmentioning
confidence: 75%
“…Wang et al recently reported that IL-12p35 regulates IL-6 through the signal transducer and activator of transcription 4 (STAT4) pathway in the inflammatory process of AAA. They also confirmed that IL-6 plays a role in inflammation in AAA (39). However, another study showed that IL-6 has a limited contribution to inflammation in AAA (37).…”
Section: Discussionmentioning
confidence: 75%
“…[ 45,46 ] In our study, an increased level of pro‐inflammatory cytokines was observed in abdominal artery segments of AAA mice, consistent with Wang's report. [ 47 ] Pirfenidone dramatically repressed the inflammation in abdominal artery segments of AAA mice, implying that pirfenidone showed a protective function on the dysfunction of the endothelium in AAA mice. Furthermore, the activated TLR4/NF‐κB signaling observed in Ang II‐treated HAECs was suppressed by pirfenidone, which further confirmed that the protective function of pirfenidone on endothelial injury might be mediated by its inhibition of NF‐κB inflammatory signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Treska et al, Cheuk et al, and Wallinder et al demonstrated that pro-inflammatory cytokines such as IL-6, IL-8, and TNF-α were upregulated in the plasma and aneurysm tissue of patients with AAA rupture ( 41 43 ). STAT signaling pathways could mediate cellular activity, including the inflammatory response, and Wang et al reported that the STAT4 signaling pathway is involved in the development and rupture of AAA ( 44 ). There are also studies demonstrating that the mTOR and VEGF signaling pathways play the important roles in the development of AAA ( 45 , 46 ), but their roles in aortic rupture remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…There is an increasing number of studies suggesting that inflammation is significantly associated with aortic rupture. Aurelian et al reported that the neutrophil-to-lymphocyte ratio (NLR) was increased in patients with aortic rupture compared to patients with intact AAAs, and an NLR of > 5 indicated a fivefold increased risk of aortic rupture (40) involved in the development and rupture of AAA (44). There are also studies demonstrating that the mTOR and VEGF signaling pathways play the important roles in the development of AAA (45, 46), but their roles in aortic rupture remain unclear.…”
Section: Xgboost Model Predicted Accuracymentioning
confidence: 99%